Aquatic invasive alien rodents in Western France: Where do we stand today after decades of control? - Manon Bonnet; Gérald Guédon; Marc Pondaven; Sandro Bertolino; Damien Padiolleau; Vanessa Pénisson; Francine Gastinel; Fabien Angot; Pierre-Cyril Renaud; Antonin Frémy; Olivier Pays (PLoS ONE)
Two aquatic invasive alien rodents, the coypu (Myocastor coypus) and muskrat (Ondatra zibethicus), have taken over a significant amount of wetlands in France. Pays de la Loire is an administrative region of about 32 000 km2 in the Western France with 6.3% of its area in wetlands (excluding the Loire River). Populations of coypus and muskrats are established and a permanent control programme has been set to reduce their impacts. The control plan is based on few professional trappers and many volunteers which makes this programme unique compared to other programme relying on professionals only. The aim of this study is to analyse the temporal and spatial dynamics of coypu and muskrat captures during the last 10 years to evaluate their effectiveness. The number of rodents removed per year increased by 50% in 10 years and reached about 288 000 individuals in 2016 with about 80% of them being coypus. During the same time length, the number of trappers involved in the programme also increased by 50% to reach 3 000 people in 2016. Although the raise of coypus and muskrats trapped can possibly be explained by an increase of the number of trappers, the number of coypus removed per trapper per year increased by 22%. Despite the outstanding number of individuals removed per year, our results suggest that the programme does not limit the population dynamics of coypus. Finally, since 2017, the number of data gathered from municipalities decreased, as did the total number of individuals trapped. Indeed, although rewards are crucial to recruit new volunteers, subsidies from local and regional authorities are declining. Decision makers and financers should be encouraged to fund this programme from the perspectives of the direct or indirect costs related to the presence of aquatic invasive alien rodents in wetlands.